A Surgical Robot Teleoperation Framework for Providing Haptic Feedback Incorporating Virtual Environment-Based Guidance - Munawar, Adnan; Fischer, Gregory (Frontiers in Robotics and AI, 2016)
In robot-assisted tele-operated laparoscopic surgeries, the patient side manipulators are controlled via the master manipulators that are controlled by the surgeon. The current generation of robots approved for laparoscopic surgery lack haptic feedback. In theory, haptic feedback would enhance the surgical procedures by enabling better coordination between the hand movements that are improved by the tactile sense of the operating environment. This research presents an overall control framework for a haptic feedback on existing robot platforms, and demonstrated on the daVinci Research Kit (dVRK) system. The paper discusses the implementation of a flexible framework that incorporates a stiffness control with gravity compensation for the surgeons manipulator and a sensing and collision detection algorithm for calculating the interaction between the patients manipulators and the surgical area.